The Relevance of the 2016 Turkish Criteria and its Implications for Determining the Beginning of the Lunar Months in Indonesia - Fairuz Sabiq; Muhammad Himmatur Riza; Masjupri Masjupri; Andi Mardian (Proceeding of the International Conference on Law and Human Rights, 2025)
The determination of the beginning of the lunar month is an important issue in religious practice and the establishment of the Hijri calendar in Indonesia. The diversity of imkan rukyat criteria used across countries necessitates an evaluation of international standards, including the 2016 Turkish Criteria, which are considered more progressive with parameters of a minimum crescent altitude of 5° and an elongation of 8°. This article examines the relevance of the 2016 Turkish Criteria within the astronomical and jurisprudential context of Indonesia, as well as its implications for the process of determining the beginning of the lunar month by the government and Islamic organizations. Through literature review, comparative astronomical analysis, and examination of hisab–rukyat practices in recent years, this study finds that the 2016 Turkish Criteria exhibit strong astronomical consistency and can enhance calendar predictability. However, its application in Indonesia may lead to discrepancies with the government’s criteria, which currently require a crescent altitude of 3° and an elongation of 6.4°. These implications include potential differences in month beginnings, the need for harmonizing criteria, and the importance of dialogue between national and international astronomical authorities. This study recommends strengthening astronomical and jurisprudential assessments prior to adopting new criteria and encourages the integration of global data to improve the accuracy of the Hijri calendar in Indonesia.